Let P 2 denote the set of all polynomials of degree two and R 3 denote the set of all vectors in three space.
Let f : P 2 → R 3 be linear transform defined by
f ( p 0 + p 1 x + p 2 x 2 ) = ⎝ ⎛ p 0 + p 1 p 1 + p 2 p 0 + p 2 ⎠ ⎞
Let
A
=
{
1
+
x
,
x
+
x
2
,
x
2
}
be a basis for
P
2
and
B
=
⎩
⎨
⎧
⎝
⎛
1
−
1
1
⎠
⎞
,
⎝
⎛
−
1
1
1
⎠
⎞
,
⎝
⎛
1
0
1
⎠
⎞
⎭
⎬
⎫
be a basis for
R
3
.
.
Let the matrix M = [ a i j ] 3 x 3 represent the linear transform above.
If λ 1 , λ 2 , λ 3 are the eigenvalues of matrix M ,
Find: ∑ j = 1 3 λ j .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The sum of the eigenvalues is the trace of the matrix, which is just − 2 3 + 0 + 1 = − 2 1 .
Problem Loading...
Note Loading...
Set Loading...
f ( 1 + x ) = ⎝ ⎛ 2 1 1 ⎠ ⎞ = α 1 ⎝ ⎛ 1 − 1 1 ⎠ ⎞ + α 2 ⎝ ⎛ − 1 1 1 ⎠ ⎞ + α 3 ⎝ ⎛ 1 0 1 ⎠ ⎞ = ⎝ ⎛ α 1 − α 2 + α 3 − α 1 + α 2 α 1 + α 2 + α 3 ⎠ ⎞
f ( x + x 2 ) = ⎝ ⎛ 1 2 1 ⎠ ⎞ = ⎝ ⎛ β 1 − β 2 + β 3 − β 1 + β 2 β 1 + β 2 + β 3 ⎠ ⎞
f ( x 2 ) = ⎝ ⎛ 0 1 1 ⎠ ⎞ = ⎝ ⎛ γ 1 − γ 2 + γ 3 − γ 1 + γ 2 γ 1 + γ 2 + γ 3 ⎠ ⎞
Solving the system:
α 1 ∗ − α 2 ∗ + α 3 ∗ = a − α 1 ∗ + α 2 ∗ = b α 1 ∗ + α 2 ∗ + α 3 ∗ = c
⟹ ⎝ ⎛ α 1 ∗ α 2 ∗ α 3 ∗ ⎠ ⎞ = ⎝ ⎜ ⎜ ⎛ 2 c − a − 2 b 2 c − a a + b ⎠ ⎟ ⎟ ⎞ ⟹
⎝ ⎛ α 1 α 2 α 3 ⎠ ⎞ = ⎝ ⎜ ⎜ ⎛ − 2 3 − 2 1 3 ⎠ ⎟ ⎟ ⎞ , ⎝ ⎛ β 1 β 2 β 3 ⎠ ⎞ = ⎝ ⎛ − 2 0 3 ⎠ ⎞ , ⎝ ⎛ γ 1 γ 2 γ 3 ⎠ ⎞ = ⎝ ⎜ ⎜ ⎛ − 2 1 2 1 1 ⎠ ⎟ ⎟ ⎞ ⟹
Matrix M = ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ − 2 3 − 2 1 3 − 2 0 3 − 2 1 2 1 1 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ⟹
M − λ I = ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ − 2 3 − λ − 2 1 3 − 2 − λ 3 − 2 1 2 1 1 − λ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣
d e t ( M − λ I ) = 0 ⟹
− 4 λ 3 − 2 λ 2 + 1 0 λ − 4 = 0 .
By inspection λ = 1 is a root of − 4 λ 3 − 2 λ 2 + 1 0 λ − 4 = 0 ⟹ ( λ − 1 ) P ( λ ) = − 4 λ 3 − 2 λ 2 + 1 0 λ − 4
Dividing we obtain: P ( λ ) = λ − 1 − 4 λ 3 − 2 λ 2 + 1 0 λ − 4 = − 4 λ 2 − 6 λ + 4 ⟹ 2 λ 2 + 3 λ − 2 = 0 ⟹ ( 2 λ − 1 ) ( λ + 2 ) = 0 ⟹ λ = − 2 , 2 1
∴ λ 1 = 1 , λ 2 = − 2 , λ 3 = 2 1 ⟹ ∑ j = 1 3 λ j = − 2 1 .